HUBUNGAN JUMLAH KENDARAAN BERMOTOR, ODOMETER KENDARAAN DAN TAHUN PEMBUATAN KENDARAAN DENGAN EMISI CO2 DI KOTA PEKANBARU - Poppy Sandra Kusumawati; Usman M Tang; Tengku Nurhidayah (Jurnal Ilmu Lingkungan, 2013)
This research has been conducted in the city of Pekanbaru , on Juni until Juli 2012. The purpose of this study was to determine the condition of the air quality in the city of Pekanbaru and the relationship between the number of motor vehicles with airconcentrations of Co2 emissions in the city of Pekanbaru. This research is expected toprovide an overview of air quality in the city of Pekanbaru, for consideration and input for Pekanbaru City Government in managing the flow of traffic on the crowded streets of thevehicle This research is expected to provide an overview of air quality in the city ofPekanbaru, for consideration and input for Pekanbaru City Government in managing theflow of traffic on the crowded streets of the vehicle and the results of this study are expectedin an effort to improve the quality of air quality, especially for reducing pollution air oncertain streets in the city of Pekanbaru.